2021
DOI: 10.3389/fgene.2021.701065
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tumor Antigens and Immune Landscape in Glioblastoma for mRNA Vaccine Development

Abstract: Background: Clinical benefits from standard therapies against glioblastoma (GBM) are limited in part due to the intrinsic radio- and chemo-resistance. As an essential part of tumor immunotherapy for adjunct, therapeutic tumor vaccines have been effective against multiple solid cancers, while their efficacy against GBM remains undefined. Therefore, this study aims to find the possible tumor antigens of GBM and identify the suitable population for cancer vaccination through immunophenotyping.Method: The genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Immune subtypes can reflect the current tumor microenvironment status of patients and the patient’s current immune status correlates with the effect of immune-related therapy ( Ye et al, 2021a ). Hence, we used immune-related genes in the TCGA-LUAD cohort to identify different patient populations and to assess their suitability for mRNA vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…Immune subtypes can reflect the current tumor microenvironment status of patients and the patient’s current immune status correlates with the effect of immune-related therapy ( Ye et al, 2021a ). Hence, we used immune-related genes in the TCGA-LUAD cohort to identify different patient populations and to assess their suitability for mRNA vaccination.…”
Section: Resultsmentioning
confidence: 99%
“…However, hub genes of immune gene co‐expression modules were not studied. Another study also used similar methods to identify tumor antigens and immune subtypes in GBM, but they did not construct the immune landscape 23 . Compared with these studies, we took a further step in the branch point analysis and identified cellular pathways that might impact on the immune status of glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are few studies on mRNA vaccines for glioma, and most of them only focused on finding tumor‐specific antigens and immunizing patients against subtypes 21–23 . Based on these findings, we further investigated mRNA vaccines for glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the development of mRNA vaccines is a hotspot in cancer immunotherapy. [33][34][35][36][37][38] We systematically analyzed gene expression and mutation in patients with CC and selected COQ2, BGN, CASP6, and FAP as potential antigens for CC mRNA vaccines. These potential antigen genes were overexpressed in tumor tissue, could encode proteins, were significantly related to prognosis, and were highly associated with APCs.…”
Section: Discussionmentioning
confidence: 99%